Correction to: Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI (European Radiology Experimental, (2023), 7, 1, (80), 10.1186/s41747-023-00394-1) - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2024)
The original article [1] omits the following funding information that the authors would like to note in this correction article: “We acknowledge financial support by Deutsche Forschungsgemeinschaft and Friedrich-Alexander-Universität Erlangen-Nürnberg within the funding programme "Open Access Publication Funding".”.
CRIS-Team Scopus Importer:2024-03-22